Strategi Dan Metode Dalam Membangun Hubungan Sehat Dan Produktif Antara Klien Dan Konselor: Perspektif Dalam Praktik Konseling - Indah Permata Bunda; Yeni Karneli; , Mudjiran (CV. ITTC INDONESIA, 2025)
The relationship between the client and counselor is a critical factor in determining the success of the counseling process. This article discusses strategies and methods for building a healthy and productive relationship, with a focus on the importance of culturally informed approaches and the consideration of individual needs. Through a literature review focusing on the context of MAN 3 Pekanbaru, this article identifies factors that influence the dynamics of the client-counselor relationship, including trust, the counselor's interpersonal skills, client characteristics, and environmental factors. Furthermore, culturally informed and individualized approaches are highlighted as essential steps in strengthening the therapeutic relationship, enhancing client engagement, and supporting the effectiveness of counseling interventions. The findings emphasize that relationships built on empathy, cultural sensitivity, and adaptation to the individual needs of clients serve as the primary foundation for the success of counseling practice.